Understanding College Athlete Mental Health: Insights from Division I Athletic Department Personnel - Newman, Tarkington; Renner, Danielle; Bessaha, Melissa; Beasley, Lauren; Kelshaw, Patricia; Cimini, Dolores; Moyer, Valerie; Lee, Levone; Ekas, Adrienne; Thorne, Kelly; Mastroleo, Nadine; Florio, Marsha (Journal of intercollegiate sport, 2025)
Throughout contemporary society, mental health and well-being are viewed as critical components of holistic, biopsychosocial development. This perspective has gained momentum within the context of sport, as athletes utilize their social platform to advocate for mental health resources and supports. However, the diverse and dynamic needs of many athletes remain unmet. Within the current study, six focus groups—which included 27 partners of collegiate athletics—were conducted and included athletes, coaches, athletic trainers, as well as athletic administrators and academic counselors. Using a reflexive thematic analysis, findings indicated that college athlete mental health is understood as holistic well-being and the ability to thrive in daily life. Participants discussed learning about mental health through academic education and training, as well as lived experiences (e.g., dual pandemic). Finally, participants believed more athletes are talking about mental health and that athletes feel most comfortable discussing mental health with their teammates and friends, the team’s sport staff (e.g., athletic trainers, strength and conditioning coaches, assistant coaches), and mental health professionals. These conversations often occurred in the locker room and on team bus rides. However, there was hesitancy discussing mental health with head coaches and because of gender differences.